Teknologi pengolahan hasil perikanan untuk meningkatkan perekonomian petani ikan di Desa Sungai Geringging, Kecamatan Kampar Kiri, Kabupaten Kampar, Riau - Sukendi Sukendi; Dewita Dewita; Thamrin Thamrin; Ridwan Manda Putra; Windarti Windarti; Eddiwan Eddiwan (Lembaga Penelitian dan Pengabdian kepada Masyarakat Universitas Riau, 2020)
The purpose of this community service activity is to provide knowledge and technology to the community from the Sinar Mentari Business Group, Sungai Geringging Village, Kampar Kiri District, Kampar Regency, in terms of processing fishery products into snack food products in the form of fish brains, fish dragon feet, and processing methods. packing and the process of presenting the resulting product better. The method used is the method of lectures, discussions, and direct practice on how to process fishery products. The results of this evaluation found that there had been a change in knowledge of 6 members of the Sinar Mentari Business Group, which showed that 5 people (83.33%) had been able to absorb the material given with a very good predicate (grade A), 1 person (16.67 %) can absorb the material given with a good predicate (B value), while those who get a sufficient predicate (C value) and poor predicate (D value) are not found. Based on the results of this evaluation, it is known that the skill level of the members of the Sinar Mentari Business group, it turns out that they have been able to process fishery products into snack food products in the form of fish brains, fish dragon legs and the process of packing as well as the process of presenting products independently and better. Meanwhile, the impact of this activity is that the housewives of Karya Mandiri Cultivator Group members have succeeded in having side activities to help their family's economy in the form of processing fish farming products.